Crisisology no more? (Comparative) Migration Studies beyond the Crisis - Nir Cohen; Tatiana Fogelman (Comparative Migration Studies)
Abstract This short intervention starts from observing a persistent, if not growing, framing of migration research – in CMS and beyond - through a concept of crisis. We contend that such an unreflexive framing, or what we call ‘crisisology’, is deeply problematic due to the reproduction of a highly skewed and binary understanding of migration. We argue that a more spatially and temporally relational approach is needed in order to dismantle such binarism. In making our argument, we first review existing critical and reflexive research on migration and crisis, while pointing out the ongoing limitations, or blind spots, of this work in moving beyond crisisology. We conclude by briefly outlining what a spatio-temporally relational approach to studying migration and ‘crisis-ness’ would entail thematically, methodologically, and conceptually.